Analisis Kinerja Penyelesaian Sengketa Informasi pada Komisi Informasi Daerah Kabupaten Cirebon - Ahmad Yusron (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
One important element in public information disclosure is the Information Commission. the information commission has a function in conducting mediation and adjudication. The Cirebon Regency Regional Information Commission is one of the commissions authorized to resolve information disputes in Cirebon Regency. the important thing in carrying out its duties is the Cirebon Regency Regional Information Commission's performance. The performance will be related to human resource competencies. The formulation of research is the competence and performance of the Secretariat and the Regional Information Commission of Cirebon Regency in resolving information disputes. The purpose of the study was to determine the competence and performance of the Secretariat and the Regional Information Commission of Cirebon Regency in resolving information disputes. This study uses a quantitative approach. The research data was taken through a questionnaire with a total sampling method from the secretariat elements and commissioners. The results obtained that human resource competencies secretariat unit and commissioner have very good competence in resolve information disputes. the performance of the secretariat and commissioners based on statistical calculations is stated to be very good.